Terminum figat: Remarks on a Difficult Phrase in the Eucharistic Prayer of the Traditio Apostolica - Bukovec, Predrag (Journal of early Christian studies, 2023)
The former communis opinio, according to which the Traditio Apostolica (TA) was a church order written by Hippolytus of Rome and representing valuable insights into third-century Roman liturgy and church discipline, has been radically questioned in recent research. The similarities between the eucharistic liturgies in TA and oriental anaphoras no longer seem to support the theory of a transregional genre in the late antique Christian West and East, but probably indicate an eastern provenance of TA itself. In addition to many currently discussed problems regarding structure and literary unity, the famous eucharistic prayer in TA 4 also bears difficulties in textual understanding: e.g., it states that Jesus Christ terminum figat during his descent into the realm of death. The motif of Christ's descent, which fortunately is quite frequently attested in the early sources, emerged in the second century. Therefore, the diachronic development of the descensus Christi can be reconstructed in its different arrangements. This is helpful in defining the "border" that Christ "established" while he visited the underworld. Some accounts of Syrian provenance seem to be the closest parallels to TA 4: here, a dramatic version of this narrative predominates, in which Death quarrels with Christ because he fears losing his inhabitants (the souls of the dead). The story culminates in a ceasefire, the end of which will be the second coming of Christ.